PRIMARY MYELOPHYBROSIS: RECOGNIZING ONCET TO COMPLICATIONS - Resti, Nimas; Rizki, Mohammad; Nurlalwani, Dita Kholida (Universitas Muhammadiyah Kalimantan Timur, 2022)
Myelofibrosis is the accumulation of scar tissue in the bone marrow so that blood cells cannot develop properly. Myeloproliferative disorders, myelofibrosis is classified into two, namely primary myelofibrosis and secondary myelofibrosis. In contrast to secondary myelofibrosis, primary myelofibrosis can occur without being preceded by myeloproliferative disorders or other diseases. In a 2013 meta-analysis study in Europe, the incidence of primary myelofibrosis (PMF) was around 0.3 per 100,000 per year. PMF may result from increased expression of inflammatory cytokines, lysyl oxidase, transforming growth factor-β, impaired megakaryocyte function, and aberrant JAK-STAT signaling. The most common clinical features found in patients with PMF are splenomegaly, hepatomegaly, fatigue, anemia, leukocytosis, and thrombocytosis. Currently the only treatment modality capable of prolonging survival or healing potential in MF is allogeneic hematopoietic stem cell transplantation (AHSCT) especially for high or very high risk patients.